Inflation Expectations and Economic Preferences - Lena Dräger; Maximilian Floto; Marina Schröder (CESifo GmbH, 2024)
We provide evidence for an expectation gap, where risk-averse as well as impatient households and experts provide significantly higher prior inflation forecasts. Using a survey randomized control trial (RCT), we can show that information about inflation forecasts closes this expectations gap. The group, whose prior expectations was farthest from the treatment information, tends to adjust posterior expectations more strongly. However, we find no such effect with respect to forecasts for energy prices, which are less informative. Our results suggest that the expectation gap seems to be partially due to differences in information seeking between different types of individuals.
Keywords: E52; E31; D84; D90; 330; inflation expectations; patience; risk preference; households; experts; survey experiment; randomized control trial (RCT)